Electrical Injury-Induced Complete Atrioventricular Block: Is Permanent Pacemaker Required?. (29th December 2015) - Beton, Osman; Efe, Tolga Han; Kaya, Hakki; Bilgin, Murat; Dinc Asarcikli, Lale; Yilmaz, Mehmet Birhan
Abstract : A considerable percentage of electrical injuries occur as a result of work activities. Electrical injury can lead to various cardiovascular disorders: acute myocardial necrosis, myocardial ischemia, heart failure, arrhythmias, hemorrhagic pericarditis, acute hypertension with peripheral vasospasm, and anomalous, nonspecific ECG alterations. Ventricular fibrillation is the most common arrhythmia resulting from electrical injury and is the leading cause of death in electrical (especially low voltage alternating current) injury cases. Asystole, premature ventricular contractions, ventricular tachycardia, conduction disorders (various degrees of heart blocks, bundle-brunch blocks), supraventricular tachycardia, and atrial fibrillation are the other arrhythmic complications of electrical injury. Complete atrioventricular block has rarely been reported and permanent pacemaker was required for the treatment in some of these cases. Herein, we present a case of reversible complete atrioventricular block due to low voltage electrical injury in a young electrical technician.